COURSE MANAGEMENT MODEL DEVELOPMENT BASED ON WORLD OF BUSINESS AND INDUSTRIES (WBI) ON LIFE SKILLS EDUCATION COURSES AND TRAINING INSTITUTIONS (LSE-CTI) (FOG-C MANAGEMENT MODEL) - Sujanto, Alex (PROCEEDING INTERNASIONAL SEMINAR, 2015)
Life Skills Education (LSE) courses management on Courses and Training Institutions (CTI) garment sewing program in Semarang Residency has been managed in accordance with management functions with the 4-in-1concept. This concept was developed into 5-in-1. The purpose of this study were: (1) to describe and analyze the factual course management models garment sewing program on LSE-CTI has been implemented, (2) develop a course management model garment sewing program based on business and world industries on LSE-CTI, (3) describe and analyze the feasibility of the model, (4) describe and analyze the effectiveness of the model.This research approach was Research and Development (R & D) with the following steps: (1) preliminary study conducted at Kartika Courses and Training Institutions in the Semarang District, Widya Busana Courses and Training Institutions in Salatiga, Muliya Courses and Training Institutions in Kendal, and Belva Courses and Training Institutions in Demak; (2) design model development validated by education management experts and practitioners through focus group discussion (FGD). (3) test the effectiveness of a hypothetical models. Data collected by observation, interviews, questionnaires and documentation. Data were analyzed using descriptive qualitative and analysis paired t-test.Results of a hypothetical model validation through field trials on a limited scale showing: (1) have a high effectiveness against upgrading course management; (2) have a high effectiveness against increase in motor competence of learners. Based on the response the manager of the Courses and Training Institutions, learners, and garment industries, the model proved to effectively improve course management.Based on this research can be concluded that the development management model of garment sewing program course based on business and world industries on Courses and Training Institutions able to increase the effectiveness of management courses for managers and learners.Keywords: Course Management, Garment Sewing Program-Based business and world industries, Life Skills Education, Courses and Training Institutions.